Analysis of serum copper and iron levels in oral submucous fibrosis patients: A case-control study - Harshal Kumar; Pramod Kumar; Sandeep Jain; Hema Suryawanshi (Wolters Kluwer Medknow Publications, 2016)
Background: Oral submucous fibrosis (OSF) is a chronic debilitating disease and a potentially malignant disorder of the oral cavity. The pathogenesis of the disease is not well established. Trace elements such as copper and iron play an important role in the pathogenesis of OSF. Estimation of these elements in serum of the patients may be helpful in understanding the pathologic mechanism. Therefore, a study was carried out to analyze the level of serum copper and iron in the population of Central India. Materials and Methods: A case-control study was carried out on 35 patients with clinically diagnosed of OSF and 35 healthy controls. OSF patients were categorized by clinical staging. Serum copper and iron concentrations were measured by atomic absorption spectrophotometry. Results: Results of the study shows that the mean serum copper concentration was greater in study group (133.3 ± 19.2) compared to control group (113.9 ± 22.1) and the mean serum iron was lower in study group (116.0 ± 24.1) compared to control group (128.2 ± 23.4). The result obtained was statistically significant. The serum copper level increases as the clinical staging of OSF progresses, whereas serum iron level decreases as clinical staging progresses. Conclusion: There was an increase in copper level and decrease in iron level in study group compared to control group; this suggests that there is an increase in copper level with the advancement of clinical staging of OSF.